Combination of Stem Cells and Rehabilitation Therapies for Ischemic Stroke - Reed Berlet; Stefan Anthony; Beverly Brooks; Zhen-Jie Wang; Nadia Sadanandan; Alex Shear; Blaise Cozene; Bella Gonzales-Portillo; Blake Parsons; Felipe Esparza Salazar; Alma R. Lezama Toledo; Germán Rivera Monroy; et al. (Biomolecules, 2021)
Stem cell transplantation with rehabilitation therapy presents an effective stroke treatment. Here, we discuss current breakthroughs in stem cell research along with rehabilitation strategies that may have a synergistic outcome when combined together after stroke. Indeed, stem cell transplantation offers a promising new approach and may add to current rehabilitation therapies. By reviewing the pathophysiology of stroke and the mechanisms by which stem cells and rehabilitation attenuate this inflammatory process, we hypothesize that a combined therapy will provide better functional outcomes for patients. Using current preclinical data, we explore the prominent types of stem cells, the existing theories for stem cell repair, rehabilitation treatments inside the brain, rehabilitation modalities outside the brain, and evidence pertaining to the benefits of combined therapy. In this review article, we assess the advantages and disadvantages of using stem cell transplantation with rehabilitation to mitigate the devastating effects of stroke.